(untitled) (Academicia Globe: Inderscience Research, 2024)
This article considers the role of parliament in the implementation of sustainable democratic reforms and trends of its development, increasing the activity of deputies in the implementation of parliamentary control, the harmfulness of increasing the participation of a deputy of the Legislative Chamber in the legislative process. and further improvement of the activities of a deputy of the Legislative Chamber to ensure the interests of political parties and citizens in the constituency.